EasyRent: a web based recommendation system for shop rental – a case study in Jitra, Kedah / Nur Azlina Ariffin and Nora Yanti Che Jan - Ariffin, Nur Azlina; Che Jan, Nora Yanti (College of Computing, Informatics and Media, UiTM Perlis, 2023)
EASYRENT: A Web Based Recommendation System For Shop Rental - A Case Study in Jitra Kedah is a system developed for the users who are involved in the property industry such as renters, landlords and admin. This system that are able to filter, prioritize and efficiently deliver relevant information about the shop in order to reduce the problem of information overload will be beneficial. The EasyRent system solves this problem by searching through a large volume of dynamically generated information to provide users with personalized content and services. This system will display all available shops to be rented where renters can filter the shops according to their preferences such as monthly rent, property type, location and many more. It will be able to assist them in making their decision. In this project, a waterfall methodology were implemented. The Waterfall methodology also known as the Waterfall model is a sequential development process that flows like a waterfall through all phases of a project. The effectiveness of the EasyRent system was evaluated through usability testing. The usability of the EasyRent system as a whole was evaluated and found to be efficient to use and satisfied most of the participants.